Implementasi Pembelajaran Berdiferensiasi pada Materi Peristiwa Sekitar Proklamasi Kemerdekaan Indonesia untuk Peserta Didik Kelas 11 di SMA Negeri 12 Semarang - Firdayanah, Rahayu Dwi; Suryadi, Andy (MUKADIMAH: Jurnal Pendidikan, Sejarah, dan Ilmu-ilmu Sosial, 2025)
This study investigates the implementation of differentiated learning in the history topic Events Around the Proclamation of Indonesian Independence for Grade XI students at SMA Negeri 12 Semarang. The central issue addressed is how teachers accommodate students' diverse learning styles, interests, and readiness levels within the historical learning process. Employing a descriptive qualitative method, the data were collected through observation, interviews, and document analysis. Findings reveal that differentiation is primarily applied in the learning product aspect, guided by students’ learning style assessments using the Aku Pintar application. Students are offered various final assignment formats—such as infographics, podcasts, or videos—aligned with their learning profiles. Despite facing technical challenges and limited instructional time, the differentiated approach successfully enhances students' motivation and comprehension. The study concludes that differentiated learning holds significant promise for fostering an inclusive and adaptive educational environment, particularly within the framework of the Merdeka Curriculum.‎